2022
DOI: 10.1007/jhep01(2022)175
|View full text |Cite
|
Sign up to set email alerts
|

Kondo line defects and affine Gaudin models

Abstract: We describe the relation between integrable Kondo problems in products of chiral SU(2) WZW models and affine SU(2) Gaudin models. We propose a full ODE/IM solution of the spectral problem for these models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 70 publications
1
29
0
Order By: Relevance
“…In the context of the Kondo problems and their relation to 4-dimensional Chern-Simons theory, these ODE take particular form which depends on the 1-form ω underlying the 4-dimensional setup. This is in agreement with the fact, mentioned in Subsection 5.4, that the 4-dimensional Chern-Simons theory is related to the so-called affine Gaudin models: indeed, it was proposed in [5] that these models can serve as a natural framework for studying the ODE/IQFT correspondence (see also [92,93,95,96] for further developments on the quantisation of affine Gaudin models and their relation to the ODE/IQFT correspondence).…”
Section: Quantisationsupporting
confidence: 84%
See 2 more Smart Citations
“…In the context of the Kondo problems and their relation to 4-dimensional Chern-Simons theory, these ODE take particular form which depends on the 1-form ω underlying the 4-dimensional setup. This is in agreement with the fact, mentioned in Subsection 5.4, that the 4-dimensional Chern-Simons theory is related to the so-called affine Gaudin models: indeed, it was proposed in [5] that these models can serve as a natural framework for studying the ODE/IQFT correspondence (see also [92,93,95,96] for further developments on the quantisation of affine Gaudin models and their relation to the ODE/IQFT correspondence).…”
Section: Quantisationsupporting
confidence: 84%
“…Let us finally mention that in the work [27], it was shown that certain integrable systems called Kondo problems can also be related to the 4-dimensional Chern-Simons theory. Quantum aspects of these systems are discussed in [27], in particular in the framework of the so-called ODE/IQFT correspondence [87][88][89][90] (see also [91] for previous results on the ODE/IQFT correspondence for Kondo problems and [92][93][94] for further recent developments). This correspondence relates certain observables of an Integrable Quantum Field Theory (IQFT), in particular the spectrum of its commuting operators, to the properties of some well-chosen Ordinary Differential Equations (ODE).…”
Section: Quantisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Renewed interest in the Kondo problem came from refs. [43,44], where some previously obtained facts concerning the isotropic case were rediscovered. Here we explain the relation between the differential equation (7.7) and the one that was considered in those works.…”
Section: Isotropic Limitmentioning
confidence: 99%
“…The IM/DE for excited states will be discussed in a companion paper. [46] 4 The su(2) Kondo line defects…”
Section: Im/de Correspondencementioning
confidence: 99%